Language Defense of Makassar Students in Jakarta, The Capital City of Indonesia - Novalia Tanasy; Nurul Fachrunnisa (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2022)
Makassar students must be able to defend their mother tongue to the language people mostly use in Jakarta. The main purpose of this investigation was to explain the Indonesian Language with Makassar Dialect (ILMD) defense by Makassar students who continue their studies in Jakarta. Analysis data was done by applying the descriptive qualitative. The data gathering technique used interviews, observation, and study of documents. The investigation was strengthened by applying strategies, namely (a) determining the focus study, (2) developing the research question, (3) collecting data, and (4) and interpreting data. The analysis data technique was investigated by applying the Spradley model. Thus, the researcher analyzed the field notes. This investigation employs steps of analysis which were (a) domain analysis, (b) taxonomy analysis, and (c) component analysis. The elucidation results explained that ILMD is used mostly in all domains among Makassar students, which indicates that ILMD is defended. Somehow, some factors are considered threats to the defense of ILMD. Hence the most threat is the prestige of the language. Therefore, the authorized must make fundamental contributions to maintain the future of ILMD to youth, especially to the students who study outside of Makassar city, such as reinforcing the Makassar youth association, so they have communities to apply ILMD regularly. Deliberately, the students should be aware of defending the ILMD to avoid language extinction while studying in Makassar.